Patterns in ETF Tracking Errors: ESG vs. Non-ESG Passive Equity Exchange-traded funds - Daniluk, Katarzyna (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: Passive exchange-traded funds (ETFs) are designed to replicate index performance but face tracking errors due to costs and market inefficiencies. ESG ETFs, which incorporate environmental, social, and governance factors, have become increasingly popular in Europe. However, limited research has examined their tracking errors patterns in comparison to non-ESG ETFs. Aim: This study is among the first to systematically assess the determinants of tracking error in passive ESG equity ETFs listed on European exchanges and compares them to non-ESG counterparts. Employing dynamic panel GMM models, we investigate key factors influencing tracking error, including past tracking error, total expense ratio (TER), assets under management (AUM), benchmark volatility, and fund age. Results: Analysing 48 ESG and 86 non-ESG equity ETFs from January 2021 to June 2024, we find that past tracking error, total expense ratio, and benchmark volatility significantly impact tracking error for both fund categories. Assets under management significantly affects tracking error only in ESG ETFs. Fund age has no significant impact in either group. These findings suggest that cost control and risk management are crucial for minimizing tracking error in both fund categories, while economies of scale play a more significant role in ESG ETFs.